Exploiting Thermochronology to Quantify Exhumation Histories and Patterns of Uplift Along the Margins of Tibet - Furlong, Kevin P.; Kirby, Eric; Creason, C. Gabriel; Kamp, Peter J. J.; Xu, Ganqing; Danišík, Martin; Shi, Xuhua; Hodges, Kip V. (Frontiers in Earth Science, 2021)
The utilization of thermal-chronological data to constrain mountain building processes exploits the links among rock uplift, exhumation, and cooling during orogenesis. Conceptually, periods of rapid uplift and associated denudation will lead to cooling of rocks as they approach Earth’s surface. The linkage between uplift and exhumation can be complex, but in practice exhumation is often assumed to directly track uplift. The reconstruction of temperature-time histories via thermochronologic systems provides a proxy method to relate the cooling of rock as it is exhumed toward the surface to orogenesis. For the rapid exhumation rates that can occur in active orogenic systems the thermal history will be complex as a result of heat advection, rates of propagation of thermal perturbations, and other processes that affect the cooling behavior. These effects become amplified as exhumation rates increase, and in regions experiencing exhumation rates greater than ~0.2-0.3 mm/yr (0.2-0.3 km/Ma) simple assumptions of cooling through a constant geotherm will bias the subsequent interpretation. Here we explore, through a suite of generalized models, the impact of exhumation rate and duration on the resulting thermal history and apparent age results. We then apply lessons from these simple exhumation systems to data sets from the high-relief ranges along the eastern margin of the Tibetan Plateau to determine exhumation histories constrained by those data. The resulting exhumation histories provide constraints on the onset of Cenozoic exhumation, the subsequent pace of exhumation, and on the tectonic history of one of the major fault systems in the central Longmen Shan.